Role and mechanism of myonectin in severe acute pancreatitis: a crosstalk between skeletal muscle and pancreas - Xiaowu Dong; Weiwei Luo; Yaodong Wang; Qingtian Zhu; Chenchen Yuan; Weiming Xiao; Weijuan Gong; Guotao Lu; Xiaolei Shi; Jin Li (Skeletal Muscle, 2024)
Abstract Background Severe acute pancreatitis (SAP) is characterized by high mortality rates and various complications, including skeletal muscle atrophy, which significantly exacerbates its outcomes. Despite its clinical relevance, the mechanistic understanding of the relationship between skeletal muscle and the pancreas in SAP remains limited. Our study aimed to elucidate this “organ crosstalk” and its potential implications. Methods We established an SAP mouse model through pancreatic duct ligation (PDL) and evaluated pancreatic necrosis, skeletal muscle atrophy, and myonectin expression levels. Recombinant myonectin protein was administered in vivo and in vitro to assess its effects on acinar cell necrosis. Mechanistic insights were gained through RNA-seq data analysis and experimental validation. Serum samples from AP patients and healthy controls were collected to investigate the correlation between serum myonectin levels and disease severity. Results The mouse model exhibited severe pancreatic necrosis, skeletal muscle atrophy, and elevated myonectin levels, with myonectin administration exacerbating model severity. We identified iron accumulation-induced ferroptosis as a key pathway contributing to myonectin-mediated acinar cell necrosis. A total of 22 healthy controls and 52 patients with varying degrees of AP were included in the serum samples and clinical data (36.5% females, age 49.79 ± 16.53). Analysis of serum samples revealed significantly higher myonectin levels in AP patients, correlating with disease severity (R = 0.28, P = 0.041). Conclusions Our findings underscore the significant role of myonectin in SAP progression and its potential as a prognostic marker for disease severity in AP patients. This study contributes to a deeper understanding of the pathophysiology of SAP and highlights potential therapeutic targets for intervention.